CLINICAL FEATURES OF JUVENILE IDIOРATHIC ARTHRITIS ONSET AND COURSE IN THE CONDITIONS OF ENVIRONMENTALLY UNFAVORABLE DONETSK REGION - Koniushevska, A.A.; Vaizer, N.V.; Pasternak, D.V.; Sydorenko, N.V.; Taran, I.D. (World of Medicine and Biology, 2019)
Juvenile idiopathic arthritis develops before the age of 16 years. It has chronic severe progressive course and, as a rule, unfavorable prognosis. The article presents clinical features of the disease onset and course, adverse prognostic factors of juvenile idiopathic arthritis. Under the conditions of the ecologically unfavorable Donetsk region, juvenile idiopathic arthritis had a severe course. Thus, two-thirds of patients had stages 2-3 of the process activity, one-fourth of patients had radiographic stages 2-3, two-thirds of patients had functional disorders class 2. Almost half of the patients had a polyarticular variant of juvenile idiopathic arthritis. More than half of children with juvenile idiopathic arthritis needed biological therapy because they had unfavorable prognostic factors for the disease course.